Quantification of Escherichia coli by kinetic 5'-nuclease polymerase chain reaction (real-time PCR) oriented to sfmD gene - Kaclíková, Eva; Pangallo, Domenico; Oravcová, Katarína; Drahovská, Hana; Kuchta, Tomáš (Letters in applied microbiology, 2005)
AIMS: A kinetic 5'-nuclease polymerase chain reaction (real-time PCR) for the quantification of Escherichia coli was developed. METHODS AND RESULTS: Specific primers and a fluorogenic probe oriented to sfmD gene, encoding a putative outer membrane export usher protein, were designed. The PCR system was highly specific and sensitive for E. coli, as determined with 37 non-E. coli strains (exclusivity, 100%) and 24 E. coli strains (inclusivity, 100%). When used in real-time PCR, linear calibration lines were obtained in the range from 10(2) to 10(8) CFU ml(-1) for three E. coli strains. Salmonella Enteritidis (10(6) CFU ml(-1)) or Citrobacter freundii (10(6) CFU ml(1)) had no effect on quantification of E. coli by the method. CONCLUSIONS: The developed real-time PCR is suitable for rapid quantification of E. coli. SIGNIFICANCE AND IMPACT OF THE STUDY: In connection to an appropriate sample preparation technique, the method is suitable for food safety and technological hygiene applications.
Keywords: deoxyribonukleasy; proteiny vnější bakteriální membrány; Food Microbiology; Kinetics; financování organizované; Escherichia coli; Bacterial Outer Membrane Proteins; Polymerase Chain Reaction; DNA, Bacterial; proteiny z Escherichia coli; DNA bakterií; Deoxyribonucleases; Financing, Organized; kinetika; Escherichia coli Proteins; potravinářská mikrobiologie; polymerázová řetězová reakce